A f r i d i i m r a n 94@yahoo.com S O L V IN G S Y ST E M S O F E Q U A T I O N S A f r i d i i m r a n 94@yahoo.com.

Slides:



Advertisements
Similar presentations
TWO STEP EQUATIONS 1. SOLVE FOR X 2. DO THE ADDITION STEP FIRST
Advertisements

Warm-Up 5 minutes Write each equation in slope-intercept form.
Solving Systems of three variables
The student will be able to:
Simultaneous Equations
The student will be able to:
(x + 4)(x + 7) = x2 + 11x + 28 (x + 14)(x + 2) = x2 + 16x + 28
DIVIDING INTEGERS 1. IF THE SIGNS ARE THE SAME THE ANSWER IS POSITIVE 2. IF THE SIGNS ARE DIFFERENT THE ANSWER IS NEGATIVE.
MULTIPLICATION EQUATIONS 1. SOLVE FOR X 3. WHAT EVER YOU DO TO ONE SIDE YOU HAVE TO DO TO THE OTHER 2. DIVIDE BY THE NUMBER IN FRONT OF THE VARIABLE.
8-2: Solving Systems of Equations using Substitution
Factoring Trinomials When a=1 ALWAYS check for GCF first! Factor trinomials in the standard form ax²+ bx + c Solve equations in the standard form ax²+
Solve Multi-step Equations
Objectives The student will be able to:
Multiply/Divide integers Absent 10/14
SYSTEMS OF EQUATIONS.
Solve by Substitution: Isolate one variable in an equation
Do Now 1/13/10 Take out HW from last night. Copy HW in your planner
 .
Solving Systems of Linear Equations By Elimination
Solve a simple absolute value equation
Use the substitution method
Use addition to eliminate a variable
Solve an equation by multiplying by a reciprocal
4.7 Complete the Square.
Solve Systems of Equations by Elimination
Part 2.  Review…  Solve the following system by elimination:  x + 2y = 1 5x – 4y = -23  (2)x + (2)2y = 2(1)  2x + 4y = 2 5x – 4y = -23  7x = -21.
4.3 Systems of Equations - Elimination Objective: The student will be able to: Solve systems of equations using elimination with addition and subtraction.
Solving a System of Equations by ELIMINATION. Elimination Solving systems by Elimination: 1.Line up like terms in standard form x + y = # (you may have.
Do Now Pass out calculators. Solve the following system by graphing: Graph paper is in the back. 5x + 2y = 9 x + y = -3 Solve the following system by using.
3.5 Solving systems of equations in 3 variables
Elimination Using Addition and Subtraction. Solving Systems of Equations So far, we have solved systems using graphing and substitution. Solve the system.
Solving Systems of Linear Equations
Warm up Add the following polynomials x + 2y = 10 5y – x = 7 + 4x – 3y = 1 + 9y + 4x = -1.
Substitution Method: 1. Solve the following system of equations by substitution. Step 1 is already completed. Step 2:Substitute x+3 into 2 nd equation.
Solving by Elimination Example 1: STEP 2: Look for opposite terms. STEP 1: Write both equations in Standard Form to line up like variables. STEP 5: Solve.
Solving Systems of Equations So far, we have solved systems using graphing and substitution. These notes show how to solve the system algebraically using.
Systems of Equations By Dr. Marinas. Solving Systems Graphing Method Substitution Method Elimination (or Adding) Method.
Multiply one equation, then add
Lesson 4-2: Solving Systems – Substitution & Linear Combinations Objectives: Students will: Solve systems of equations using substitution and linear combinations.
Objective solve systems of equations using elimination.
3-2: Solving Systems of Equations using Elimination
Elimination Method - Systems. Elimination Method  With the elimination method, you create like terms that add to zero.
Solving a System of Equations by ELIMINATION. Elimination Solving systems by Elimination: 1.Line up like terms in standard form x + y = # (you may have.
objective I Can state the first step for solving systems. I Can solve systems of equations by graphing, substitution or elimination.
Objective I can solve systems of equations using elimination with addition and subtraction.
Solve Systems of Equations by Elimination
The student will be able to:
Solve Systems of Equations by Elimination
Solve a system of linear equation in two variables
3.5 Solving systems of equations in 3 variables
Solving Systems of Equations using Substitution
Simultaneous Equations
The student will be able to:
The student will be able to:
The student will be able to:
Solving Systems of Equations
Solving a System of Equations in Two Variables by the Addition Method
The student will be able to:
The student will be able to:
Solving Systems of Equations
Example 2B: Solving Linear Systems by Elimination
SOLVING SYSTEMS OF EQUATIONS.
The student will be able to:
Simultaneous Equations
The Substitution Method
The student will be able to:
Step 1: Put the equations in Standard Form. Standard Form: Ax + By = C
Solving Systems of Equations:
SOLVING SYSTEMS OF EQUATIONS.
SOLVING SYSTEMS OF EQUATIONS.
Presentation transcript:

A f r i d i i m r a n 94@yahoo.com S O L V IN G S Y ST E M S O F E Q U A T I O N S A f r i d i i m r a n 94@yahoo.com

BY GRAPHING Y = 2X + 1 Y = -X + 4   (1,3) IS THE SOLUTION

Graphing is not the only way to solve a system of equations Graphing is not the only way to solve a system of equations. It is not really the best way because it has to be graphed perfectly and some answers are not integers. SOOOO We need to learn another way!!!!

Solve: by ELIMINATION x + y = 12 -x + 3y = -8 Like variables must be lined under each other. Solve: by ELIMINATION x + y = 12 -x + 3y = -8 4y = 4 We need to eliminate (get rid of) a variable. The x’s will be the easiest. So, we will add the two equations. Divide by 4 y = 1 THEN----

Now check our answers in both equations------ Substitute your answer into either original equation and solve for the second variable. X +Y = 12 x + 1 = 12 -1 -1 x = 11 (11,1) Answer Now check our answers in both equations------

X + Y =12 11 + 1 = 12 12 = 12 -x + 3y = -8 -11 + 3(1) = -8 -11 + 3 = -8 -8 = -8

Solve: by ELIMINATION 5x - 4y = -21 -2x + 4y = 18 Like variables must be lined under each other. Solve: by ELIMINATION 5x - 4y = -21 -2x + 4y = 18 3x = -3 We need to eliminate (get rid of) a variable. The y’s be will the easiest.So, we will add the two equations. Divide by 3 x = -1 THEN----

Now check our answers in both equations------ Substitute your answer into either original equation and solve for the second variable. 5X - 4Y = -21 5(-1) – 4y = -21 -5 – 4y = -21 5 5 -4y = -16 y = 4 (-1, 4) Answer Now check our answers in both equations------

5x - 4y = -21 5(-1) – 4(4) = -21 -5 - 16 = -21 -21 = -21 -2(-1) + 4(4) = 18 2 + 16 = 18 18 = 18

Solve: by ELIMINATION 2x + 7y = 31 5x - 7y = - 45 Like variables must be lined under each other. Solve: by ELIMINATION 2x + 7y = 31 5x - 7y = - 45 7x = -14 We need to eliminate (get rid of) a variable. The y’s will be the easiest. So, we will add the two equations. Divide by 7 x = -2 THEN----

Now check our answers in both equations------ Substitute your answer into either original equation and solve for the second variable. 2X + 7Y = 31 2(-2) + 7y = 31 -4 + 7y = 31 4 4 7y = 35 y = 5 (-2, 5) Answer Now check our answers in both equations------

2x + 7y = 31 2(-2) + 7(5) = 31 -4 + 35 = 31 31 = 31 5x – 7y = - 45 5(-2) - 7(5) = - 45 -10 - 35 = - 45 - 45 =- 45

Solve: by ELIMINATION x + y = 30 x + 7y = 6 Like variables must be lined under each other. Solve: by ELIMINATION x + y = 30 x + 7y = 6 We need to eliminate (get rid of) a variable. To simply add this time will not eliminate a variable. If one of the x’s was negative, it would be eliminated when we add. So we will multiply one equation by a – 1.

X + Y = 30 X + Y = 30 -X – 7Y = - 6 ( X + 7Y = 6 ) -1 -6Y = 24 - 6 - 6 Now add the two equations and solve. - 6 - 6 Y = - 4 THEN----

Now check our answers in both equations------ Substitute your answer into either original equation and solve for the second variable. X + Y = 30 X + - 4 = 30 4 4 X = 34 (34, - 4) Answer Now check our answers in both equations------

x + y = 30 34 + - 4 = 30 30 = 30 x + 7y = 6 34 + 7(- 4) = 6 34 - 28 = 6 6 = 6

Solve: by ELIMINATION x + y = 4 2x + 3y = 9 Like variables must be lined under each other. Solve: by ELIMINATION x + y = 4 2x + 3y = 9 We need to eliminate (get rid of) a variable. To simply add this time will not eliminate a variable. If there was a –2x in the 1st equation, the x’s would be eliminated when we add. So we will multiply the 1st equation by a – 2.

( ) -2 Y = 1 THEN---- X + Y = 4 -2X - 2 Y = - 8 2X + 3Y = 9 Now add the two equations and solve. THEN----

Now check our answers in both equations------ Substitute your answer into either original equation and solve for the second variable. X + Y = 4 X + 1 = 4 - 1 -1 X = 3 (3,1) Answer Now check our answers in both equations------

x + y = 4 3 + 1 = 4 4 = 4 2x + 3y = 9 2(3) + 3(1) = 9 6 + 3 = 9 9 = 9